Co-creating Value through Car Experience Trips: An Exploratory Study of the International Car Industry - Hartley, Stephanie (2011)
In the light of economic recession, car brands (marques) and dealerships are using experience trips and events in order to maintain sales momentum, due to many luxury purchases being placed on hold by individuals concerned about their finances. Building on existing experiential marketing theory and pulling together underlying theories of Service-Dominant Logic and the co-creation of value, this exploratory paper assesses how experience trips and events are used in the car industry in order to co-create value. Using case study and interview findings from the event organiser and the experience day attendees, factors such as experience centres, learning, skills and knowledge, and brand advocacy reveal how value is created for a given marque. The paper also seeks to explore how similar experience marketing techniques could be employed in emerging markets such as China. Although experiences are brand-specific and customised, potential international customers could benefit from experience trips provided by luxury car marques. The paper also highlights how luxury purchases can form part of our identity, with individuals’ aspirations influencing how experiences are developed in order to continue creating value for a given marque.